A prospective study of relationship between medial joint pain and mild knee osteoarthritis - Dadarya, Brajesh; Sirsikar, Ashish; Vidyarthi, Ashok (International Journal of Research in Orthopaedics, 2018)
Background: The relationship between joint pain and osteoarthritis is poorly understood, however, the most common patterns associated with knee osteoarthritis are diffuse or medial joint pain. The objective of the study was to test the sensitivity of medial knee joint pain for the diagnosis of mild knee osteoarthritis, and thence its relationship. Methods: This is a prospective analytical study of 124 patients visiting to our out-patient setup in the year 2017, with complaint of medial knee joint pain, which after thorough clinical examination, were investigated radiologically. Results: In our study of 124 patients, there were 69 female (55.5%) and 55 male (47.5%), with a mean age of 59.3 years. The average duration of symptoms was 3.2 years, and the average VAS for severity of pain was 59.3. The sensitivity of medial knee joint pain for mild OA was thus calculated to be 79.8%. Conclusions: Medial knee joint pain is a very important symptom to raise a suspicion and also to warrant further radiological investigation for the early diagnosis and management of knee OA.